Collaborating with transgender youth to educate healthcare trainees and professionals: randomized controlled trial of a didactic enhanced by brief videos - Martin, Andrés; Celentano, Jillian; Olezeski, Christy; Halloran, Justin; Penque, Brent; Aguilar, Jemel; Amsalem, Doron (BMC Public Health, 2022)
In collaboration with members of the transgender and gender diverse (TGD) community, we created a didactic resource about the unique needs of TGD youth.
0 citations (Crossref) [2023-10-31]
Keywords: Adolescents; Gender-diverse; Health; Health education; Mental health; Transgender; dept.mft; dept.swk; peer-reviewed

Well-Being and Prosperity: Multidirectional Disciplinary Interactions with Religion - Morais, M.; Karakunnel, J.J.; Perumbilly, S.; Yeon, G.; Rassendren, G. (Journal of Dharma, 2022)
Despite significant advancements in science and technology, religion continues to influence human lives. The twentieth-century perspectives from social sciences, influenced by the secular hypothesis, mainly highlight the negative influence of religion on human progress and practically ignore its influential and positive impact on various fields of knowledge/disciplines. In this paper, we have examined literature from politics, economics, and psychology to understand religion’s impact on these disciplines and vice versa. We find that religion’s contribution to human society in the 20th and 21st centuries has been mostly positive, especially in education, healthcare, social justice, economic growth, ethics, and initiatives for eradicating inequality and injustice. For instance, religion provides effective coping measures and strategies when humans face uncertainties and catastrophes and facilitate comfort, confidence, and emotional wellness. Further, we realised that (i) the contemporary research literature in social sciences generally highlights the interaction between religion and various fields of knowledge in a unidirectional way —i.e., religion influencing disciplines and not how disciplines influence religion, and (ii) that it fails to reveal a more complex multidirectional and circular relationship between religion and social sciences. This paper proposes ways to bring together social scientists and religious scholars to facilitate the much-needed discussion on the multidirectional relationship between religion and social sciences, thereby paving the way toward the well-being of individuals and social transformation. © 2022 Journal of Dharma: Dharmaram Journal of Religions and Philosophies (DVK, Bangalore),.
Keywords: and well-being; charitable giving; circularity; dept.mft; linearity; peer-reviewed; political participation; religion; sustainable development; ⛔ No DOI found